Salt-rejecting 3D cone flowing evaporator based on bilayer photothermal paper for high-performance solar seawater desalination - Chen, Yu-Qiao; Zhu, Ying-Jie; Wang, Zhong-Yi; Yu, Han-Ping; Xiong, Zhi-Chao (Journal of colloid and interface science, 2024)
A bilayer photothermal paper-based 3D cone flowing evaporator with high solar light absorption, low water evaporation enthalpy and excellent salt-rejecting performance is fabricated using multilayered MXene, ultralong hydroxyapatite nanowires, and hydrophilic polymers. The 3D cone flowing evaporator cooperates with a siphon effect-driven unidirectional fluid transportation unit to guide concentrated saline flows out from the evaporating surface, leading to high water evaporation rate and salt-rejecting stable seawater desalination performance. [Display omitted] •A bilayer photothermal paper-based cone flowing water evaporator is reported.•The evaporator exhibits excellent properties for solar seawater desalination.•The evaporator exhibits much higher water evaporation rate than most reported values.•The evaporator can effectively prevent salt accumulation on the evaporating surface. Solar energy-driven water evaporation technology is a promising, low-cost and sustainable approach to alleviate the global clean water shortage, but usually suffers from low water evaporation rate and severe salt deposition on the water evaporation surface. In this work, a hydrophilic bilayer photothermal paper-based three-dimensional (3D) cone flowing evaporator was designed and prepared for stable high-performance seawater desalination with excellent salt-rejecting ability. The as-prepared bilayer photothermal paper consisted of MXene (Ti3C2Tx) and HAA (ultralong hydroxyapatite nanowires, poly(acrylic acid), and poly(acrylic acid-2-hydroxyethyl ester)). The accordion-like multilayered MXene acted as the efficient solar light absorber, and ultralong hydroxyapatite (HAP) nanowires served as the thermally insulating and supporting skeleton with a porous networked structure. A siphon effect-driven unidirectional fluid transportation unit in the 3D cone flowing evaporator could guide the concentrated saline flowing away from the evaporating surface to prevent salt deposition on the evaporation surface, avoiding severe deterioration of the performance in solar water evaporation. Furthermore, combining high solar light absorption and high photothermal conversion efficiencies, low water evaporation enthalpy (1838 ± 11 J g−1), and additional energy taken from the ambient environment, the as-prepared cone flowing evaporator exhibited a high water evaporation rate of 3.22 ± 0.20 kg m−2 h−1 for real seawater under one sun illumination (1 kW m−2), which was significantly higher than many values reported in the literature. This study provides an effective approach for designing high-performance solar energy-driven water evaporators for sustainable seawater desalination and wastewater purification.